Mesophyll conductance to CO2 and leaf morphological characteristics under drought stress during Quercus ilex L. resprouting - Fleck, Isabel; Peña-Rojas, Karen; Aranda, Xavier (Annals of Forest Science, 2010)
• Quercus ilex L., the dominant species in Mediterranean forests and one with a great capacity for resprouting after disturbances, is threatened by the expected increase in ﬁre frequency and drought associated with climate change. • The aim of this study was to determine the contribution of photosynthesis limitants, especially mesophyll conductance (gmes ) during this species’ resprouting and under summer drought. • Resprouts showed 5.3-fold increased gmes and 3.8-fold increased stomatal conductance (gs ) at midday with respect to leaves of undisturbed individuals. With increased drought, structural changes (decreased density and increased thickness) in resprouts contributed to the observed higher photosynthesis and increased gmes . However, gmes only partially depended on leaf structure, and was also under physiological control. Resprouts also showed lower non-stomatal limitations (around 50% higher carboxylation velocity (Vc,max) and capacity for ribulose-1,5-bisphosphate regeneration (Jmax)). A signiﬁcant contribution of gmes to leaf carbon isotope discrimination values was observed. • gmes exhibits a dominant role in photosynthesis limitation in Q. ilex and is regulated by factors other than morphology. During resprouting after disturbances, greater capacity to withstand drought, as evidenced by higher gmes , gs and lower non-stomatal limitants, enables increased photosynthesis and rapid growth.
Keywords: carbon isotopic composition; leaf structure; mesophyll conductance; photosynthesis limitants; Quercus ilex

Photosynthesis and resource distribution through plant canopies - Niinemets, Uelo (PLANT CELL AND ENVIRONMENT, 2007)
Plant canopies are characterized by dramatic gradients of light between canopy top and bottom, and interactions between light, temperature and water vapour deficits. This review summarizes current knowledge of potentials and limitations of acclimation of foliage photosynthetic capacity (A(max)) and light-harvesting efficiency to complex environmental gradients within the canopies. Acclimation of A(max) to high light availability involves accumulation of rate-limiting photosynthetic proteins per unit leaf area as the result of increases in leaf thickness in broad-leaved species and volume: total area ratio and mesophyll thickness in species with complex geometry of leaf cross-section. Enhancement of light-harvesting efficiency in low light occurs through increased chlorophyll production per unit dry mass, greater leaf area per unit dry mass investment in leaves and shoot architectural modifications that improve leaf exposure and reduce within-shoot shading. All these acclimation responses vary among species, resulting in species-specific use efficiencies of low and high light. In fast-growing canopies and in evergreen species, where foliage developed and acclimated to a certain light environment becomes shaded by newly developing foliage, leaf senescence, age-dependent changes in cell wall characteristics and limited foliage re-acclimation capacity can constrain adjustment of older leaves to modified light availabilities. The review further demonstrates that leaves in different canopy positions respond differently to dynamic fluctuations in light availability and to multiple environmental stresses. Foliage acclimated to high irradiance respond more plastically to rapid changes in leaf light environment, and is more resistant to co-occurring heat and water stress. However, in higher light, co-occurring stresses can more strongly curb the efficiency of foliage photosynthetic machinery through reductions in internal diffusion conductance to CO2. This review demonstrates strong foliage potential for acclimation to within-canopy environmental gradients, but also highlights complex constraints on acclimation and foliage functioning resulting from light x foliage age interactions, multiple environmental stresses, dynamic light fluctuations and species-specific leaf and shoot structural constraints.
Keywords: acclimation kinetics; age effects; foliage aggregation; leaf longevity; leaf structure; light acclimation; nitrogen content; support costs; tocopherol content; xanthophyll cycle

Photosynthesis and resource distribution through plant canopies - Niinemets, Uelo (PLANT CELL AND ENVIRONMENT, 2007)
Plant canopies are characterized by dramatic gradients of light between canopy top and bottom, and interactions between light, temperature and water vapour deficits. This review summarizes current knowledge of potentials and limitations of acclimation of foliage photosynthetic capacity (A(max)) and light-harvesting efficiency to complex environmental gradients within the canopies. Acclimation of A(max) to high light availability involves accumulation of rate-limiting photosynthetic proteins per unit leaf area as the result of increases in leaf thickness in broad-leaved species and volume: total area ratio and mesophyll thickness in species with complex geometry of leaf cross-section. Enhancement of light-harvesting efficiency in low light occurs through increased chlorophyll production per unit dry mass, greater leaf area per unit dry mass investment in leaves and shoot architectural modifications that improve leaf exposure and reduce within-shoot shading. All these acclimation responses vary among species, resulting in species-specific use efficiencies of low and high light. In fast-growing canopies and in evergreen species, where foliage developed and acclimated to a certain light environment becomes shaded by newly developing foliage, leaf senescence, age-dependent changes in cell wall characteristics and limited foliage re-acclimation capacity can constrain adjustment of older leaves to modified light availabilities. The review further demonstrates that leaves in different canopy positions respond differently to dynamic fluctuations in light availability and to multiple environmental stresses. Foliage acclimated to high irradiance respond more plastically to rapid changes in leaf light environment, and is more resistant to co-occurring heat and water stress. However, in higher light, co-occurring stresses can more strongly curb the efficiency of foliage photosynthetic machinery through reductions in internal diffusion conductance to CO2. This review demonstrates strong foliage potential for acclimation to within-canopy environmental gradients, but also highlights complex constraints on acclimation and foliage functioning resulting from light x foliage age interactions, multiple environmental stresses, dynamic light fluctuations and species-specific leaf and shoot structural constraints.
The following values have no corresponding Zotero field: pub-location: 9600 GARSINGTON RD, OXFORD OX4 2DQ, OXON, ENGLAND publisher: BLACKWELL PUBLISHING
Keywords: acclimation kinetics; age effects; foliage aggregation; leaf longevity; leaf structure; light acclimation; nitrogen content; support costs; tocopherol content; xanthophyll cycle

Complex adjustments of photosynthetic potentials and internal diffusion conductance to current and previous light availabilities and leaf age in Mediterranean evergreen species Quercus ilex - NIINEMETS, Ü L. O.; CESCATTI, ALESSANDRO; RODEGHIERO, MIRCO; TOSENS, TIINA (Plant, Cell & Environment, 2006)
Mature non-senescent leaves of evergreen species become gradually shaded as new foliage develops and canopy expands, but the interactive effects of integrated light during leaf formation (QintG), current light (QintC) and leaf age on foliage photosynthetic competence are poorly understood. In Quercus ilex L., we measured the responses of leaf structural and physiological variables to QintC and QintG for four leaf age classes. Leaf aging resulted in increases in leaf dry mass per unit area (MA), and leaf dry to fresh mass ratio (DF) and decreases in N content per dry mass (NM). N content per area (NA) was independent of age, indicating that decreases in NM reflected dilution of leaf N because of accumulation of dry mass (NA = NM MA). MA, DF and NA scaled positively with irradiance, whereas these age-specific correlations were stronger with leaf growth light than with current leaf light. Area-based maximum ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) carboxylase activity (VcmaxA), capacity for photosynthetic electron transport (JmaxA) and the rate of non-photorespiratory respiration in light (RdA) were also positively associated with irradiance. Differently from leaf structural characteristics, for all data pooled, these relationships were stronger with current light with little differences among leaves of different age. Acclimation to current leaf light environment was achieved by light-dependent partitioning of N in rate-limiting proteins. Mass-based physiological activities decreased with increasing leaf age, reflecting dilution of leaf N and a larger fraction of non-photosynthetic N in older leaves. This resulted in age-dependent modification of leaf photosynthetic potentials versus N relationships. Internal diffusion conductance (gm) per unit area (gmA) increased curvilinearly with increasing irradiance for two youngest leaf age classes and was independent of light for older leaves. In contrast, gm per dry mass (gmM) was negatively associated with light in current-year leaves. Greater photosynthetic potentials and moderate changes in diffusion conductance resulted in greater internal diffusion limitations of photosynthesis in higher light. Both area- and mass-based gm decreased with increasing leaf age. The decrease in diffusion conductance was larger than changes in photosynthetic potentials, leading to larger CO2 drawdown from leaf internal air space to chloroplasts (ΔC) in older leaves. The increases in diffusion limitations in older leaves and at higher light scaled with age- and light-dependent increases in MA and DF. Overall, our study demonstrates a large potential of foliage photosynthetic acclimation to changes in leaf light environment, but also highlights enhanced structural diffusion limitations in older leaves that result from leaf structural acclimation to previous rather than to current light environment and accumulation of structural compounds with leaf age.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CO2 drawdown; growth irradiance; leaf age; leaf structure; mesophyll conductance; nitrogen content; photosynthetic capacity

Complex adjustments of photosynthetic potentials and internal diffusion conductance to current and previous light availabilities and leaf age in Mediterranean evergreen species Quercus ilex - NIINEMETS, Ü L O; CESCATTI, ALESSANDRO; RODEGHIERO, MIRCO; TOSENS, TIINA (Plant, Cell & Environment, 2006)
Mature non-senescent leaves of evergreen species become gradually shaded as new foliage develops and canopy expands, but the interactive effects of integrated light during leaf formation (QintG), current light (QintC) and leaf age on foliage photosynthetic competence are poorly understood. In Quercus ilex L., we measured the responses of leaf structural and physiological variables to QintC and QintG for four leaf age classes. Leaf aging resulted in increases in leaf dry mass per unit area (MA), and leaf dry to fresh mass ratio (DF) and decreases in N content per dry mass (NM). N content per area (NA) was independent of age, indicating that decreases in NM reflected dilution of leaf N because of accumulation of dry mass (NA = NM MA). MA, DF and NA scaled positively with irradiance, whereas these age-specific correlations were stronger with leaf growth light than with current leaf light. Area-based maximum ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) carboxylase activity (VcmaxA), capacity for photosynthetic electron transport (JmaxA) and the rate of non-photorespiratory respiration in light (RdA) were also positively associated with irradiance. Differently from leaf structural characteristics, for all data pooled, these relationships were stronger with current light with little differences among leaves of different age. Acclimation to current leaf light environment was achieved by light-dependent partitioning of N in rate-limiting proteins. Mass-based physiological activities decreased with increasing leaf age, reflecting dilution of leaf N and a larger fraction of non-photosynthetic N in older leaves. This resulted in age-dependent modification of leaf photosynthetic potentials versus N relationships. Internal diffusion conductance (gm) per unit area (gmA) increased curvilinearly with increasing irradiance for two youngest leaf age classes and was independent of light for older leaves. In contrast, gm per dry mass (gmM) was negatively associated with light in current-year leaves. Greater photosynthetic potentials and moderate changes in diffusion conductance resulted in greater internal diffusion limitations of photosynthesis in higher light. Both area- and mass-based gm decreased with increasing leaf age. The decrease in diffusion conductance was larger than changes in photosynthetic potentials, leading to larger CO2 drawdown from leaf internal air space to chloroplasts (ΔC) in older leaves. The increases in diffusion limitations in older leaves and at higher light scaled with age- and light-dependent increases in MA and DF. Overall, our study demonstrates a large potential of foliage photosynthetic acclimation to changes in leaf light environment, but also highlights enhanced structural diffusion limitations in older leaves that result from leaf structural acclimation to previous rather than to current light environment and accumulation of structural compounds with leaf age.
Keywords: CO2 drawdown; growth irradiance; leaf age; leaf structure; mesophyll conductance; nitrogen content; photosynthetic capacity

Structural and functional traits of Quercus ilex in response to water availability - Bussotti, Filippo; Bettini, Davide; Grossoni, Paolo; Mansuino, Silvia; Nibbi, Renzo; Soda, Costanza; Tani, Corrado (Environmental and Experimental Botany, 2002)
Water potential and morpho-anatomical parameters were measured, during the course of 1 year, on leaves of Quercus ilex trees growing in two coastal stands in Tuscany (Central Italy) with different conditions of water availability: Colognole (CL, mesic site) and Cala Violina (CV, xeric site). Morpho-anatomical measurements included: general leaf features and sclerophylly indices (surface area, thickness, mass per area and density), leaf moisture indices (water content, relative water content, succulence) and histochemical analysis (detection and localization of cutine and tannins in the leaves and starch reserves in the twigs). During the warmest and driest period (August) pre-dawn water potential (pd ) in Holm-oak leaves reached −2.7 MPa at CV and −0.6 MPa at CL. Leaf surface was lower (−34%) and total leaf thickness (+10%), as well as spongy-palisade parenchyma ratio (+20%) were higher at CV. The sclerophylly parameters (leaf mass per area and leaf tissue density) were higher at CV than at CL (+24% leaf mass per area and +19% leaf tissue density). Among the moisture parameters, water content was higher at CL (+8%) and succulence was higher at CV (+13%). No differences in relative water content were observed between the two sites. All the parameters considered were substantially stable during the study period, with the exception of relative water content at CL, that ﬂuctuated within the year. Histochemical analysis revealed a greater thickness of the upper cuticular layer at CV, whereas there were no differences in tannin distribution and content between the two sites. Differences in starch storage were detected in branchlets: it was abundant in CV but very scarce at CL. The strategies of Quercus ilex to cope with water stress were discussed at morpho-structural level.
Keywords: leaf structure; starch; Tannins; water potential

Structural and functional traits of Quercus ilex in response to water availability - Bussotti, Filippo; Bettini, Davide; Grossoni, Paolo; Mansuino, Silvia; Nibbi, Renzo; Soda, Costanza; Tani, Corrado (Environmental and Experimental Botany, 2002)
Water potential and morpho-anatomical parameters were measured, during the course of 1 year, on leaves of Quercus ilex trees growing in two coastal stands in Tuscany (Central Italy) with different conditions of water availability: Colognole (CL, mesic site) and Cala Violina (CV, xeric site). Morpho-anatomical measurements included: general leaf features and sclerophylly indices (surface area, thickness, mass per area and density), leaf moisture indices (water content, relative water content, succulence) and histochemical analysis (detection and localization of cutine and tannins in the leaves and starch reserves in the twigs). During the warmest and driest period (August) pre-dawn water potential (pd ) in Holm-oak leaves reached −2.7 MPa at CV and −0.6 MPa at CL. Leaf surface was lower (−34%) and total leaf thickness (+10%), as well as spongy-palisade parenchyma ratio (+20%) were higher at CV. The sclerophylly parameters (leaf mass per area and leaf tissue density) were higher at CV than at CL (+24% leaf mass per area and +19% leaf tissue density). Among the moisture parameters, water content was higher at CL (+8%) and succulence was higher at CV (+13%). No differences in relative water content were observed between the two sites. All the parameters considered were substantially stable during the study period, with the exception of relative water content at CL, that ﬂuctuated within the year. Histochemical analysis revealed a greater thickness of the upper cuticular layer at CV, whereas there were no differences in tannin distribution and content between the two sites. Differences in starch storage were detected in branchlets: it was abundant in CV but very scarce at CL. The strategies of Quercus ilex to cope with water stress were discussed at morpho-structural level.
Keywords: leaf structure; starch; Tannins; water potential